What Made Sahar Scared?: Imaginary and Realistic Causes in Palestinian and American Children’s Concept for Fear - Kayyal, Mary H.; Widen, Sherri C. (2015)
Young children associate fear with monsters, ghosts, and other imaginary creatures more than with real threats to safety, such as robbers or bullies – at least in Western societies. Cross-cultural studies are rare, are limited to older children, and have not asked if the role of the imagination extends to emotions other than fear. In this study, young Palestinian and American children (60 in each group, 3–7 years, age- and sex-matched) were asked to tell stories in which they generated a cause for fear as well as happiness, sadness, anger and surprise. Imaginary creatures were rarely cited as the cause of any emotion other than fear, but were cited frequently for fear by both Palestinians and Americans. There was also a cultural difference: Palestinians generated significantly fewer imaginary and more realistic causes for fear than did Americans. Thus, imaginary causes are a part of Palestinian children’s fear concept, but imaginary causes are not primary as they are for American children; for Palestinian children, realistic causes are primary in their fear concept.
Keywords: Culture -- emotion -- fear -- situational causes